Macrocnemis gracilis, a new genus and species of Idiocnemidinae (Zygoptera: Platycnemididae) from Papua New Guinea - Theischinger, G.; Gassmann, D.; Richards, S. J. (Zootaxa, 2015)
A new genus and species belonging to the damselfly subfamily Idiocnemidinae from Papua New Guinea, Macrocnemis gracilis gen. nov. sp. nov. is described and illustrated. It is the largest known member of the Papuan idiocnemidine radiation, and its affinities to existing genera remain unclear. The new taxon is currently known with certainty only from small streams flowing through mid-montane rainforest in the Hindenburg Range of Papua New Guinea’s rugged central cordillera.